En la orilla, by Rafael Chirbes: the re-reading of the Spanish Civil Was from the post-memory perspective - Serber, Daniela Cecilia (Caracol, 2016)
In Rafael Chirbes’ novels, the recent Spanish past is not only the scene for its characters, but a functional element in the construction of the final message. Even considering the “memory boom” often remarked by literary criticism, in which, sometimes, he is contextualized, we think that his texts reveal his compromise with History and, therefore, that they propose a way of (re)reading and (re)writing History for repairing discursive voids born during the Francisco Franco´s dictatorship, but prolonged during the democratic Transition. Spanish republicans and “their” Civil War are one of the historical “pauses” that Chirbes wanted to reactivate. In En la orilla, he intends to do so through Esteban’s eyes, a child during the war, and his father, a carpenter republican former combatant, who decides to remain silent for the rest of his life.